Proceedings of the 39th International Symposium on Lattice Field Theory β€” PoS(LATTICE2022) 2022
DOI: 10.22323/1.430.0316
|View full text |Cite
|
Sign up to set email alerts
|

Chiral extrapolation of hadronic vacuum polarization and isospin-breaking corrections

Abstract: By far the biggest contribution to hadronic vacuum polarization (HVP) arises from the two-pion channel. Its quark-mass dependence can be evaluated by combining dispersion relations with chiral perturbation theory, providing guidance on the functional form of chiral extrapolations, or even interpolations around the physical point. In addition, the approach allows one to estimate in a controlled way the isospin-breaking (IB) corrections that arise from the pion mass difference. As an application, we present an u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…been compared to a phenomenological evaluation of isospin-breaking effects in Refs. [82][83][84][85][86], which found that the lattice calculation of these contributions cannot be the source of the discrepancy. Whether radiative corrections on the experimental side could provide an explanation of the puzzle is the subject of ongoing research [87][88][89][90][91].…”
Section: Tablementioning
confidence: 99%
“…been compared to a phenomenological evaluation of isospin-breaking effects in Refs. [82][83][84][85][86], which found that the lattice calculation of these contributions cannot be the source of the discrepancy. Whether radiative corrections on the experimental side could provide an explanation of the puzzle is the subject of ongoing research [87][88][89][90][91].…”
Section: Tablementioning
confidence: 99%
“…the channel 0 + opens in QCD+QED and also close to other thresholds (see Refs. [15,16]). Nevertheless, we notice that in order to explain the observed tension at ∼ 0.8 GeV and ∼ 0.6 GeV an isospin breaking effect larger than 2% would be needed and this is hard to reconcile with the first principle lattice calculation performed in Ref.…”
Section: Pos(lattice2022)307mentioning
confidence: 99%
“…Puzzles in the hadronic contributions to the muon anomalous magnetic moment has been compared to a phenomenological evaluation of isospin-breaking effects in Refs. [81][82][83][84][85], which found that the lattice calculation of these contributions cannot be the source of the discrepancy. Whether radiative corrections on the experimental side could provide an explanation of the puzzle is the subject of ongoing research [86][87][88][89][90].…”
Section: Pos(fpcp2023)042mentioning
confidence: 99%